The Effectiveness Of Giving Peppermint Oil Aromatherapy On The Severity Of Nausea And Vomiting In Pregnant Women Trimester I At Health Puskemas Tulang Bawang 1 - Safitri, Wayan Maya; Astriana, Astriana; Evayanti, Yulistiana (JKM (Jurnal Kebidanan Malahayati), 2024)
ABSTRACTIn Indonesia, as many as 50%-75% of pregnant women experience nausea and vomiting in the first trimester or early pregnancy (Harahap, 2020). The number of pregnancies in Lampung Province in 2019 was 118,241 mothers, with the highest pregnancy in Central Lampung Regency as many as 19,211 and the lowest in Pesisir Barat Regency as many as 1,421 while Tulang Bawang Regency with 11,121 being in the top 5. The purpose of this study was to determine the effectiveness of peppermint oil aromatherapy on the severity of nausea and vomiting in TM I pregnant women at the Tulang Bawang 1 Health Center in 2022.This type of research is quantitative, with a pre-experimental research design. The population was TM I pregnant women who experienced nausea and vomiting, the sampling technique in this study was purposive sampling, univariate and bivariate data analysis using t-test, the study was conducted at the Tulang Bawang 1 Health Center in June 2022.The average of nausea and vomiting in pregnant women before being given peppermint aromatherapy with a mean of 10.30. The average nausea and vomiting in pregnant women after being given peppermint aromatherapy with a mean of 6.90. The results of statistical tests obtained p-value = 0.000 which means that there is an effectiveness of giving peppermint oil aromatherapy to the severity of nausea and vomiting in pregnant women with TM I at the Tulang Bawang 1 Health Center in 2022. Pregnant women who complain of nausea and vomiting in the first trimester should do peppermint oil aromatherapy appropriately in order to reduce nausea and vomiting in the first trimester.Keywords : Peppermint Oil, Nausea and Vomiting, Pregnant Women